Kinship networks of seed exchange shape spatial patterns of plant virus diversity - Marc Delêtre; Jean-Michel Lett; Ronan Sulpice; Charles Spillane (Nature Communications, 2021)
This study combines ethnobotanical and epidemiological data to understand how social networks of seed exchange influence the genetic structure of the African cassava mosaic virus in Gabon. Results reveal contrasted patterns of viral diversity in patrilineal and matrilineal communities, consistent with cultural differences in modes of seed exchange.